Perilaku Pengguna Sistem Dompet Digital di Masa Pandemi Covid-19 - Richo Diana Aviyanti (Jurnal Akuntansi dan Pajak, 2022)
The Covid-19 pandemic forces people to adapt to changes in behavior, one of which is payment behavior. Transactions with digital wallets can be considered as a physical distancing mechanism that can minimize the risk of spreading viruses. Therefore, this study aims to obtain empirical evidence on the effect of performance expectancy, effort expectancy, social influence, perceived trust, and facilitating conditions for intention in using the digital wallet system during the Covid-19 pandemic. The research was conducted in Malang City, Indonesia. Data was collected through an online questionnaire which 262 active users of the OVO digital wallet filled in directly. This research is quantitative research with a positive paradigm. The analysis method used is a structural equation regression model (Structural Equation Modeling / SEM) with a Partial Least Square/PLS test tool. Empirical evidence shows that performance expectancy, social influence, and perceived trust positive affect intention in using digital wallets. Meanwhile, effort expectancy and facilitating conditions do not have that impact. Digital wallets can be used as a safer payment alternative during the Covid-19 pandemic. Therefore, digital wallet platform can increase consumer trust by providing a safe and useful system to meet their needs. Digital wallet platform can also take advantage of the social environment and social media to share information to form positive perceptions. Keywords: Digital Wallet, intention, information system, UTAUT, Covid-19.